Effects of livestock grazing on rangeland grasshopper (Orthoptera: Acrididae) abundance - O’Neill, Kevin M; Olson, Bret E; Rolston, Marni G; Wallander, Roseann; Larson, Deanna P; Seibert, Catherine E (Agriculture, ecosystems & environment, 2003)
Livestock may impact habitat quality for grasshoppers by reducing food availability and by altering microclimate and potential oviposition sites. A 5-year study was conducted to create consistent grazing impacts on replicated plots and measure their effects on plant cover, microclimate, and grasshopper abundance. Cattle were used to produce two levels of grazing intensity that were compared to ungrazed controls. Differences in plant cover were greatest immediately after grazing each summer, grasshopper microhabitats tending to be shadier, cooler, less windy, and more humid in the ungrazed plots. The grasshopper assemblage included five of the worst pest grasshopper species in North America: Ageneotettix deorum, Aulocara elliotti, Melanoplus sanguinipes, M. packardii, and Camnula pellucida. Most species had greater abundance on ungrazed pastures, particularly during the 4–6 weeks after grazing each year. However, A. elliotti was often more abundant in heavily grazed areas early in the year when early instars were present and in late summer when adults were predominant. There was no strong evidence that the effect of grazing on grasshopper abundance increased over the 5-year study. At this time, all changes in grasshopper numbers cannot be directly attributed to particular habitat characteristics that changed after grazing, but the results suggest that grazing management could be used to reduce pest grasshopper densities.